An open-label phase II trial of sotrovimab (VIR-7831) prophylaxis against COVID-19 infection in immunocompromised individuals with impaired SARS-CoV-2 humoral immunity - Isabel H. Gonzalez-Bocco; Rayven Frierson; Alyssa Cho; Fabiola A. Reyes Curcio; Andres E. Franceschi; Chloe Lahoud; Dimitrios G. Moshovitis; Katherine Beluch; Manu Balusu; C. Elizabeth Keleher; Keri M. Sullivan; Michael Dougan; et al. (New Microbes and New Infections)
Background: Immunocompromised individuals have a limited humoral immune response to SARS-CoV-2 vaccination and are at higher risk of severe COVID-19. Sotrovimab is a monoclonal antibody (mAb) targeting a conserved SARS-CoV-2 spike protein epitope. Methods: This phase II open-label study evaluated the safety and tolerability of sotrovimab pre-exposure prophylaxis in immunocompromised adults with impaired vaccine response. Between February and June 2022 in the northeastern region of the USA, participants received sotrovimab 500 mg IV on Treatment Day (TD) 1 and 2000 mg IV on TD2 due to the spread of the Omicron BA.2 subvariant. Follow-up lasted 36 weeks (∼5 half-lives), assessing safety and tolerability, PK, COVID-19 incidence and severity, and quality of life. Results: Ninety-three subjects received 500 mg on TD1, of whom 81 received 2000 mg on TD2. Three patients reported five drug-related adverse events, four grade 2 infusion-related reactions and one grade 2 headache, all resolving quickly. Among 35 SARS-CoV-2 cases, 94 % had no activity limitations or hospitalizations per the National Institute of Allergy and Infectious Diseases Ordinal Scale. Sotrovimab exhibited dose-dependent increases in exposures at doses of 500 mg and 2000 mg. Conclusion: Sotrovimab pre-exposure prophylaxis had a favorable safety profile and was well tolerated at both doses, with low immunogenicity. These findings support mAbs’ safety as COVID-19 pre-exposure prophylaxis in this population.